TANGGUNG JAWAB SOSIAL PROFESI PENDIDIKAN TERHADAP LINGKUNGAN MASYARAKAT - Risa Rahma Wely; Haris Riadi; Al Asfuri (Jurnal Manajemen Pendidikan, 2026)
This study aims to examine the social responsibility of the education profession towards the community environment, addressing the need to understand how educators, education personnel, and school principals contribute beyond academic duties, given that the education profession is still often perceived as limited to classroom instruction. The research used a literature review, with data collection carried out through citations from various sources such as books, scientific journals, articles, and relevant documents. Meanwhile, the data analysis technique used descriptive qualitative methods. The results indicate that the social responsibility of the education profession is manifested in three main dimensions, namely as a professional educator, a moral role model, and an agent of social change. The study also identifies several challenges faced by educators in fulfilling this responsibility, including inclusive education, limited resources, psychological pressures, external demands, and teacher welfare. By implementing these three dimensions, the education profession can make a significant contribution in creating a society with character, quality, and noble morals. Strengthening this social responsibility therefore needs to be a shared concern in supporting the achievement of national education goals.